Pneumococcal Colonization and Virulence Factors Identified Via Experimental Evolution in Infection Models. (27th January 2021) - Green, Angharad E; Howarth, Deborah; Chaguza, Chrispin; Echlin, Haley; Langendonk, R Frèdi; Munro, Connor; Barton, Thomas E; Hinton, Jay C D; Bentley, Stephen D; Rosch, Jason W; Neill, Daniel R
Abstract: Streptococcus pneumoniae is a commensal of the human nasopharynx and a major cause of respiratory and invasive disease. We examined adaptation and evolution of pneumococcus, within nasopharynx and lungs, in an experimental system where the selective pressures associated with transmission were removed. This was achieved by serial passage of pneumococci, separately, in mouse models of nasopharyngeal carriage or pneumonia. Passaged pneumococci became more effective colonizers of the respiratory tract and we observed several examples of potential parallel evolution. The cell wall-modifying glycosyltransferase LafA was under strong selection during lung passage, whereas the surface expressed pneumococcal vaccine antigen gene pvaA and the glycerol-3-phosphate dehydrogenase gene gpsA were frequent targets of mutation in nasopharynx-passaged pneumococci. These mutations were not identified in pneumococci that were separately evolved by serial passage on laboratory agar. We focused on gpsA, in which the same single nucleotide polymorphism arose in two independently evolved nasopharynx-passaged lineages. We describe a new role for this gene in nasopharyngeal carriage and show that the identified single nucleotide change confers resistance to oxidative stress and enhanced nasopharyngeal colonization potential. We demonstrate that polymorphisms in gpsA arise and are retained during human colonization. These findings highlight how within-host environmental conditions can determine trajectories of bacterial evolution. Relative invasiveness or attack rate of pneumococcal lineages may be defined by genes that make niche-specific contributions to bacterial fitness. Experimental evolution in animal infection models is a powerful tool to investigate the relative roles played by pathogen virulence and colonization factors within different host niches.